Increased serum leptin level in overweight patients with colon carcinoma: A cross-sectional and prospective study - Wang, Di; Gao, Lichen; Gong, Kuiyu; Chai, Qin; Wang, Guihua (Molecular and clinical oncology, 2017)
Leptin is associated with carcinogenesis and progression of various cancers. However, the changes of the serum leptin level in Chinese overweight patients with colon carcinoma and its association with response to treatment in these patients have rarely been investigated. A total of 63 Chinese overweight patients with colon cancer and 40 body mass index-matched control subjects were recruited in the present study. The serum leptin levels of colon cancer patients prior to and 21 days after colectomy, as well as those of healthy controls, were measured and compared. In addition, the focal expression of phosphorylated Akt, mammalian target of rapamycin and 70S6 Kinase (p-Akt, p-mTOR and P-70S6 Kinase) and leptin were determined in the resected specimens and the correlation between serum leptin levels and the focally expressed markers were investigated. The serum leptin levels of colon cancer patients were significantly higher compared with those of the controls (22.67±12.56 vs. 12.68±7.8 ng/ml, respectively; P<0.05). Moreover, the leptin levels decreased after the operation when compared to the preoperative levels (18.67±8.54 vs. 22.67±12.56 ng/ml, respectively; P<0.05). In addition, there was a significant correlation between the serum leptin levels and the focal expression of p-Akt, p-mTOR, P-70S6 Kinase and leptin (P<0.05). In conclusion, the leptin levels were elevated in Chinese overweight patients with colon cance these levels decreased following colectomy, indicating that leptin may be associated with colon carcinogenesis. Thus, serum leptin level may be used for early diagnosis and for monitoring the response to treatment of colon carcinoma in overweight Chinese patients.